Otolith morphometrics for growth and conservation assessment of endangered Napoleon wrasse (Cheilinus undulatus) in Sabah, Malaysia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Gunawan EH, Fui CF, Tuzan AD, Kadar NA, Pratiwy FM, Buwono ID,  Senoo S. 2025. Otolith morphometrics for growth and conservation assessment of endangered Napoleon wrasse (Cheilinus undulatus) in Sabah, Malaysia. Biodiversitas 26: 5770-5779. The endangered Napoleon wrasse (Cheilinus undulatus) plays a vital role as a carnivorous fish in coral reef ecosystems. However, it faces severe threats from overfishing and habitat degradation, necessitating evidence-based conservation strategies. This study assessed growth pattern, biological condition, and size structure by integrating fish morphometric and otolith metrics from 41 specimens collected in Eastern Sabah, Malaysia. Fish total length from 27.51 to 103.88 cm (mean SD = 35.28±11.72 cm) and body weight from 330.24 to 19400.85 g (mean SD = 757.32±2934.41 g). Linear regression revealed a near-isometric length-weight relationship (b = 3.062, 95% CI [2.904, 3.219], r² = 0.975, p
Keywords: Condition factor, coral reef fisheries, endangered species, length-weight relationship, sustainable management